2011
DOI: 10.1108/07363761111150026
|View full text |Cite
|
Sign up to set email alerts
|

Impulse purchases of groceries in France and Sweden

Abstract: PurposeThe purpose of this paper is to identify similarities and differences with regard to factors affecting consumers' impulse purchases of groceries in France and Sweden.Design/methodology/approachData were collected by a random survey of 202 Swedish and 368 French households. MANCOVA is the principal analytical technique.FindingsThe analysis indicates that, while Swedish shoppers make more impulse purchases, the French consumers appear to be more attentive to special in‐store displays and two‐for‐the‐price… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 19 publications
1
32
0
5
Order By: Relevance
“…Consumer's propensity to purchase on impulse receives a further impetus when they see an item on sale (Ramaswamy and Namakumar, 2009). Hulten & Vanyushyn (2011) also observed that impulsive buyers are giving more attention to the in-store displays and combo offerings.…”
Section: External Stimuli and Store Environmentmentioning
confidence: 88%
“…Consumer's propensity to purchase on impulse receives a further impetus when they see an item on sale (Ramaswamy and Namakumar, 2009). Hulten & Vanyushyn (2011) also observed that impulsive buyers are giving more attention to the in-store displays and combo offerings.…”
Section: External Stimuli and Store Environmentmentioning
confidence: 88%
“…Por outro lado, outros estudos mostram não haver diferenças entre homens e mulheres na compra por impulso, e tampouco indicam que a variável sexo seja capaz de prever a propensão a comprar por impulso (e.g., Barkley-Levenson & Fox, 2016;Hultén & Vanyushyn, 2011).…”
Section: Diferenças Sexuais Na Compra Por Impulsounclassified
“…The perception of value created by discounted prices and other promotions, allows the consumer to overcome their mental barriers to impulse purchases. [14] The other four variables of Buyer Emotions, Traits, Demographics and Store Atmospherics were found to have weak correlations with Impulsive Buying Behaviour. Store Atmospherics was found to have a correlation of only 0.16.…”
Section: Discussionmentioning
confidence: 89%
“…Promotional low prices or other benefits were found to help consumers overcome the mental barriers to Impulsive Buying Behaviour. While discounted prices, 2-for-1 offerings or special store displays were all found to be equally effective in triggering purchase [26]. Discounted prices were found to be the most commonly tool to promote impulsive purchases.…”
Section: F Promotion (P)mentioning
confidence: 91%